KRITIKAL FAKTOR SUKSES PENGELOLAAN OPERASI DAN PEMELIHARAAN IRIGASI TERHADAP INSFRASTRUKTUR IRIGASI DI KOTA PAYAKUMBUH - Yeri Siswanto; Nusyaifi Yulius (Ensiklopedia of Journal, 2019)
Payakumbuh City is one of the largest rice / rice producing cities in West Sumatra province, so one step to meet the air needs needed to support the sustainability of rice agriculture, the Payakumbuh city government built irrigation infrastructure. The Regional Government of Payakumbuh has also made various efforts to build irrigation networks that have been built by allocating a budget each year. But various irrigation networks that have been built repair damage and are not well maintained, allowing the network to supply air for agriculture cannot be launched. Causal factors This condition occurs because the network of plantations that have been built has not been maintained and managed systemically. For this reason, an efficient and effective system management is needed, by knowing what key factors are needed in the construction of a good operating and maintenance system.